Pengaruh Gender, Locus of Control, Kompleksitas Tugas, dan Pengalaman Auditor Terhadap Audit Judgement - Setyawan, Diki; Pahala, Indra; Handarini, Dwi (Jurnal Akuntansi, Perpajakan dan Auditing, 2023)
An auditor is a profession whose job is to reveal the truth of the information contained in a company's financial reports. Audit judgment is the auditor's decision on an idea, opinion, event, status and others that will influence the audit opinion. This research was conducted with the aim of obtaining empirical evidence regarding Gender, Locus of Control, Task Complexity, and auditor experience in the Application of Audit Judgment. This research uses primary data with a sample of internal auditors representing BPKP DKI Jakarta Province. The sampling technique in this research used convenience sampling with 70 respondents. Hypothesis testing in this research uses Structural Model Partial Least Square (SEM-PLS) using SmartPLS 3.0 software. Based on the results of the analysis in this research, it can be concluded that: (1) gender has a negative effect on audit judgment, (2) locus of control has a positive effect on audit judgment, (3) task complexity has a negative effect on audit judgment, and (4) Auditor Experience has a positive effect on audit judgment.